A Bibliometric Review of Global Research on Human Resource Management and Supply Chain Management - Rashed Mahmud Shakil; Md. Alamgir Mollah; Shawkat Tanveer Rahman; Md. Mamun Habib (International Journal of Supply Chain Management, 2020)
Human resource management (HRM) and supply chain management (SCM) play a growingly vital role in the organizational prosperity and economic development of countries that accelerate the importance of tracing the trajectory relating to this emerging field. However, till recently, limited number of research has examined the evolution of HRM-SCM research quantitatively. Aiming to provide an overall insight into the research in HRM-SCM field, this study utilized science mapping tools for analysing 469 articles from Scopus database explicitly related to HRM-SCM research. This bibliometric review aimed at documenting the size, geographic distribution of relevant literature, and growth trajectory, identifying key authors, journals, and documents, highlighting emerging topics, and analysing the intellectual structure of HRM-SCM knowledge base. Being the first bibliometric analysis on HRM-SCM research, this review is intended to provide a key reference for researchers entering this field, along with guidance regarding high value frameworks, and foci for further research.